2022
DOI: 10.1111/iej.13676
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of societal and professional impact of Endodontology research articles: A multivariate scientometric analysis

Abstract: Aim To identify factors that are predictive of short‐term professional and societal impact of research within the specialty of Endodontology and to identify the top‐10 articles that achieved the greatest societal impact and describe their characteristics. Methodology Research articles in the field of Endodontology published in 2019 were eligible for inclusion, with the sample identified using Medline. Following screening of titles and abstracts, bibliometric data of the identified articles were exported into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…(2019) analyzed the impact of funding on innovation according to the performance of patents and concluded that federal support accelerates the production of innovation. And more recently, Doğramaci and Rossi-Fedele (2022) suggested that publication typology and journal impact factor were significant predictors of short-term social and academic impact of endodontic research articles. Non grant-funded research and the coverage in general news bulletins achieved higher social impact, while the social attention score was also strongly related to professional impact.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) analyzed the impact of funding on innovation according to the performance of patents and concluded that federal support accelerates the production of innovation. And more recently, Doğramaci and Rossi-Fedele (2022) suggested that publication typology and journal impact factor were significant predictors of short-term social and academic impact of endodontic research articles. Non grant-funded research and the coverage in general news bulletins achieved higher social impact, while the social attention score was also strongly related to professional impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We analyze in this paper the effect of both funding and OA on social attention. There are other studies that evaluated the effect of funding on social attention (Doğramaci and Rossi-Fedele, 2022) or the effect of OA on social attention (Yu et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a simple example, in dentistry, if we compare two specialties (e.g. orthodontics [21] versus endodontics [22]), we will have different values. Ultimately, these differences can result in more funding for fields with higher scientometric values.…”
Section: Plos Onementioning
confidence: 99%
“…In 1973, he compiled a list of the 25 most cited articles published by science and technology journals [8], while one of his later analyses focused on the 100 most cited 'chemical' articles [9]. Subsequently, similar present-day citation analyses were applied to many other subjects including endodontics to retrieve information from many aspects of the subjects analyzed, such as collaboration patterns, research trends, national research performance and predictors of citation numbers [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only two studies have investigated the altmetric features of endodontic articles. Neither of these studies examined letters in endodontics [15,35]. Therefore, this study aimed to identify the 100 top-cited letters in endodontics and analyze their bibliometric and altmetric features.…”
Section: Introductionmentioning
confidence: 99%